A mini review on percent time-spent-following (PTSF) as the service measure for two-lane highways - Rizana, Rama; Alhajyaseen, Wael (Communications in Science and Technology, 2018)
Percent Time Spent Following (PTSF) is used by the Highway Capacity Manual (HCM) as one of the service measures to assess the level-of-service of two-lane highways since the 2000 edition. But, the problem facing to estimate this parameter is that the difficulty to measure it directly in the field. From several studies, it is known that the HCM analytical procedures applied in PTSF estimation produces inconsistent results with the 3 s surrogate measure and most of them are overestimate. This paper presents a review on estimating PTSF on two-lane highways from several studies that adopted HCM procedures.